Perlindungan Hukum Terhadap Anak Dibawah Umur Sebagai Korban Prostitusi Online Melalui Aplikasi Michat Studi Kasus Putusan Nomor 563/PID.SUS/2023/PN.SRG - I Nyoman Gede Sugiartha; I Nyoman Gede Bayu Krisnantha Dwipayana; I Nyoman Subamia (Fakultas Hukum Universitas Warmadewa, 2024)
Children are human beings who are under the age where they clearly do not deserve to be used as objects of deviant acts and other inhumane things. However, the facts on the ground show that child exploitation is still rampant in this country. Therefore, this study wants to discuss the legal protection arrangements for minors involved in online prostitution victims through the MiChat application and how the judge's consideration in the decision against minors as victims of online prostitution. The methods used in this research are statutory, case, and conceptual approaches as well as normative legal research. After the research runs, the results of the legal protection arrangements for prostitution of minors who are victims of online prostitution are contained in Article 66 No.35/2014 concerning Amendments to Law No. 23/2002 concerning Child Protection. The results of this study indicate that the judge's decision against the pimp decided the sentence based on Article 83 Jo Article 76 f of Indonesian Law No. 35/2014 concerning Amendments to Indonesian Law No. 23/2002 concerning Child Protection because he had trafficked minors who were victims of online prostitution.